2008
DOI: 10.1029/2007jd009433
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying above‐cloud aerosol using spaceborne lidar for improved understanding of cloudy‐sky direct climate forcing

Abstract: Estimates of global mean direct climate forcing by absorbing aerosols located above boundary layer clouds are large, uncertain, and almost entirely unconstrained by observations. Spaceborne lidar offers a new opportunity for global constraints. Here we examine techniques for using liquid water clouds as lidar targets, allowing aerosol optical depth and Ångström exponent to be deduced directly from aerosol effects on light transmission. Two such techniques are examined using data from the Cloud‐Aerosol Lidar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(133 citation statements)
references
References 54 publications
4
129
0
Order By: Relevance
“…All three models show an aerosol layer above the low clouds in the Canarian region, consistent with observations (Chand et al, 2008;Devasthale and Thomas, 2011;Waquet et al, 2013;Winker et al, 2013), with a contribution of 50 % to the total AOD. Figure 8 shows vertical cross sections of the aerosol extinction coefficient at 550 nm and the vertically resolved cloud fraction for the model MIROC, in the Canarian region, as an example, and an aerosol layer co-located with the cloud layer as well as an overlying aerosol layer is evident for all four experiments.…”
Section: Vertical Aerosol and Cloud Distributionssupporting
confidence: 67%
See 1 more Smart Citation
“…All three models show an aerosol layer above the low clouds in the Canarian region, consistent with observations (Chand et al, 2008;Devasthale and Thomas, 2011;Waquet et al, 2013;Winker et al, 2013), with a contribution of 50 % to the total AOD. Figure 8 shows vertical cross sections of the aerosol extinction coefficient at 550 nm and the vertically resolved cloud fraction for the model MIROC, in the Canarian region, as an example, and an aerosol layer co-located with the cloud layer as well as an overlying aerosol layer is evident for all four experiments.…”
Section: Vertical Aerosol and Cloud Distributionssupporting
confidence: 67%
“…However, the cloud brightening shows no clear dependence on the vertical distribution of the aerosols. Dust aerosols above the clouds are found in the Canarian region, but BC aerosols are not found to be prevalent above the clouds in the biomass burning regions, which may be expected from observations (Chand et al, 2008;Devasthale and Thomas, 2011;Waquet et al, 2013;Winker et al, 2013) and which may further counteract the cloud brightening. Hence, the darkening effect of the anthropogenic non-sulfate aerosols is not strong enough in the models to counteract the brightening effect of the background aerosol, leaving climate models with predominantly positive gradients in disagreement with satellite observations .…”
Section: Discussionmentioning
confidence: 91%
“…Some studies suggest that significant biases may exist in some regions, when satellite measurements only for cloud-free conditions are assimilated into a model (Reid et al, 2004;Zhang and Reid, 2009). Partial constraints on the aerosol load above clouds could be obtained using the emerging satellite observations of AOD above clouds from CALIOP lidar Hu et al, 2007;Chand et al, 2008) and even passive sensors like POLDER, OMI, and MODIS (Waquet et al, 2009;Torres et al, 2012;Jethva et al, submitted for publication;Yu et al, 2012b). This new capability needs to be explored.…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…In an intercomparison of above-cloud AOD from A-Train satellites sensors, Jethva et al (2014) found that the CALIPSO-derived above-cloud AOD was consistently lower than those derived from the other satellites sensors in the A-Train. Chand et al (2008) and Liu et al (2015) both used alternative retrieval methods to the standard CALIPSO algorithm to derive AOD above clouds specifically. Other efforts to quantify abovecloud AOD from passive satellite sensors include the works by e.g., Knobelspiesse et al (2011), Meyer et al (2013, Torres et al (2012), and Waquet et al (2009Waquet et al ( , 2013.…”
Section: E Chung Et Al: Relationship Between Low-cloud Presence mentioning
confidence: 99%